Students' Knowledge of Applied Anesthesiology Nursing level 3 ITEKES Bali on ECG Interpretation - I Nyoman Tripayana; Emanuel Ileatan Lewar; Yustina, yusniawati; I Gde Agus Shuarsedana Putra (Poltekkes Kemenkes Kupang, 2025)
Background: Electrocardiography (ECG) records the electrical activity of the atria and ventricles and forms characteristic ECG waves. It is essential for diagnosing cardiovascular diseases. Bali Province has a high prevalence of cardiovascular diseases (1.3% or approximately 16,481 people), which requires all health workers, especially anesthetists, to not only perform ECG installation but also interpret the results accurately. This study aimed to determine the knowledge of level 3 Anesthesiology Nursing students at ITEKES Bali regarding ECG interpretation. Methods: This research uses quantitative research with this was a descriptive quantitative study with a cross-sectional design. The output of this research can be used as a source of information or evaluation material for teachers and students regarding the importance of interpreting ECGs. Results: The results of this study show that most students (90.0%) had good knowledge of ECG interpretation, while 10.0% had sufficient knowledge. Conclusion: The knowledge possessed by ITEKES Bali level 3 Anesthesiology Nursing students regarding ECG interpretation was good and sufficient.